Iraqi diplomatic activity in Spain 1950-1958 (historical study) (Journal of the College of Basic Education, 2023)
The study, tagged Iraqi diplomatic activity in Spain from 1950 to 1958, sheds light on the activity and activities of the Iraqi embassy in Madrid, which began to operate since 1950 and managed by three Iraqi ambassadors who had a major role in strengthening relations between the two friendly countries and represented their country in the most wonderful way. As well as political and consular services for Iraqis and Arabs residing in Spain. The Iraqi diplomatic mission in Spain has faced many obstacles in the midst of the tense international situation, so the Palestinian and Algerian issues were the focus of the mission's work, and it was able on many occasions to support these two issues financially and morally, and it succeeded in defining European public opinion in general and the Spanish in particular the right of the Arabs to support their just and fateful causes.